Ethnobotanical study and traditional knowledge on Tibetan wooden bowls in Benzilan Town, Yunnan, China - Wei Liu; Qing Huang; Shicai Shen; Lun Yin (Journal of Ethnobiology and Ethnomedicine)
Abstract Background The Tibetan wooden bowls are common utensils and feature obvious Tibetan cultural traits. However, research on Tibetan wooden bowls is limited, especially the ethnobotanical study related to wooden bowl production. This study will explore the traditional knowledge related to the use of plants in the production of Tibetan wooden bowls as well as the cultural connotations and social significance of these bowls in Benzilan Town through an ethnobotanical investigation. Materials and methods In August 2024 and March 2025, we employed key informant interviews, semi-structured interviews, and participatory observations to conduct an ethnobotanical investigation of Tibetan wooden bowls in Benzilan Town. Also, we used relative frequency of citation (RFC) and informant consensus factors (ICF) to indicate the different perceptions of different vocational groups and villages in terms of plants used as raw materials. And we documented and analyzed the plants used to lacquer and dye through participatory observation. Result We recorded a total of 18 plant species used in different stages of Tibetan wooden bowl production, belonging to 16 families, of which 13 plant species are used as raw materials, and 6 plant species are used for lacquering and dyeing. Among these plant species, Taxus yunnanensis (can be used as both raw material and dye material) and Torreya yunnanensis are under official protection due to their rarity. All the raw materials are collected from these plants in a reasonable manner. Conclusion The skilled craftsmen of Benzilan Town possess a wealth of traditional knowledge about Tibetan wood bowl making. This traditional knowledge not only promotes the sustainable use of resources but also contributes to the preservation and inheritance of traditional wood bowl crafting techniques. Furthermore, Tibetan wooden bowls, as important handicrafts, have not only driven the development of ethnic tourism but also stimulated the local economy. More importantly, the flourishing of the Tibetan wooden bowl industry not only helps preserve and pass down Tibetan culture but also fosters the dissemination of Tibetan culture. This case study may also encourage other similar regions to pay more attention to their local traditional handicrafts and provide a basis for subsequent studies.